Centre‐level variation in behaviour and the predictors of behaviour in 5‐year‐old children with non‐syndromic unilateral cleft lip: The Cleft Care UK study. Part 5. (June 2017) - Waylen, A.; Mahmoud, O.; Wills, A. K.; Sell, D.; Sandy, J. R.; Ness, A. R.
Structured Abstract: Objectives: The aims of this study were to describe child behavioural and psychosocial outcomes associated with appearance and speech in the Cleft Care UK (CCUK) study. We also wanted to explore centre‐level variation in child outcomes and investigate individual predictors of such outcomes. Setting and sample population: Two hundred and sixty‐eight five‐year‐old children with non‐syndromic unilateral cleft lip and palate (UCLP) recruited to CCUK. Materials and methods: Parents completed the Strengths and Difficulties questionnaire (SDQ) and reported their own perceptions of the child's self‐confidence. Child facial appearance and symmetry were assessed using photographs, and intelligibility of speech was derived from audio‐visual speech recordings. Centre‐level variation in behavioural and psychosocial outcomes was examined using hierarchical models, and associations with clinical outcomes were examined using logit regression models. Results: Children with UCLP had a higher hyperactive difficulty score than the general population. For boys, the average score was 4.5 vs 4.1 ( P =.03), and for girls, the average score was 3.8 vs 3.1 ( P =.008). There was no evidence of centre‐level variation for behaviour or parental perceptions of the child's self‐confidence. There is no evidence of associations between self‐confidence and SDQ scores and either facial appearance or behaviour. Conclusions: Children born with UCLP have higher levels of behaviour problems than the general population.